Simulation and Analysis of PV Module Performance by Innovative Sorting Methods - Yusufoglu, U.A.; Min, B.; Pletzer, T.M.; van Mölken, J.I.; Kurz, H. (Energy procedia, 2012)
Sorting of solar cells is a vital step to achieve the predetermined power out of the photovoltaic module, nevertheless there is a lack of detailed investigations of all relevant parameters defining the global module efficiency. Sorting methods tend to rely on simple electrical parameters such as PMAX, IMPP, and ISC. However, it is crucial to take into consideration that the performance of individual cells will be changed after the encapsulation. Therefore, in this study potential changes in operating parameters such as JSC and Rser are integrated in the sorting step. It is a fact that at low light intensities the impact of Rshunt on module performance is more critical compared to standard test conditions (STC) where the actual measurements are carried out. In addition, the optical parameters of cells are subject to change after the encapsulation. That is why, inclusion of optical parameters such as reflectance into the sorting step is analysed. In this study, innovative sorting methods with the inclusion of Rshunt and reflectance were introduced. The results show that, at low light intensities conventional sorting approach can be extended with a combination of Rshunt and other electrical parameters to achieve higher module efficiencies up to 0.1% absolute. In addition, adding optical reflectance into the sorting parameters set current mismatches in modules can be minimized.